Pengaruh Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Torabika Coffe Pt Cipta Niaga Semesta (Mayora Group) Di Punggur - Putri, Eka Buana; Nasikah, Durotun (Jurnal Manajemen DIVERSIFIKASI, 2021)
Abstract In business activities in this globalization era, technological developments are needed to expand business networks. The level of competition that is quite tight makes business actors more innovative in carrying out marketing activities for their products and services. This study aims to determine the effect of product quality, price, service quality on purchasing decisions at Torabika Coffee Pt Cipta Niaga Semesta (Mayora Group) in Punggur. This type of research is quantitative data analysis and in this study using descriptive analysis methods to collect data in the field by taking samples from a population of 96 respondents to all consumers who buy Torabika Coffe at Pt Cipta Niaga Semesta (Mayora Group) in Punggur. Test requirements analysis using the normality test, linearity test and homogeneity test. Testing the analysis model using multiple regression models, partial test (t test), simultaneous test (F test), and the coefficient of determination (R2). And using statistical hypothesis testing. Based on the results of research with multiple linear regression analysis with t test, it was found that product quality had a positive and significant effect on purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch, while price had a negative and significant effect on purchasing decisions, and service quality had a negative and insignificant effect. against purchasing decisions on purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch. From the F test, it is obtained that the product quality, price, and service quality together have a positive and significant influence on purchasing decisions on purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch. Keywords: Product Quality, Price, and Service Quality Against Purchasing Decisions In purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch. Abstract In business activities in this globalization era, technological developments are needed to expand business networks. The level of competition that is quite tight makes business actors more innovative in carrying out marketing activities for their products and services. This study aims to determine the effect of product quality, price, service quality on purchasing decisions at Torabika Coffee Pt Cipta Niaga Semesta (Mayora Group) in Punggur. This type of research is quantitative data analysis and in this study using descriptive analysis methods to collect data in the field by taking samples from a population of 96 respondents to all consumers who buy Torabika Coffe at Pt Cipta Niaga Semesta (Mayora Group) in Punggur. Test requirements analysis using the normality test, linearity test and homogeneity test. Testing the analysis model using multiple regression models, partial test (t test), simultaneous test (F test), and the coefficient of determination (R2). And using statistical hypothesis testing. Based on the results of research with multiple linear regression analysis with t test, it was found that product quality had a positive and significant effect on purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch, while price had a negative and significant effect on purchasing decisions, and service quality had a negative and insignificant effect. against purchasing decisions on purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch. From the F test, it is obtained that the product quality, price, and service quality together have a positive and significant influence on purchasing decisions on purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch. Keywords: Product Quality, Price, and Service Quality Against Purchasing Decisions In purchasing decisions at Torabika Coffe at Pt Cipta Niaga Semesta punggur branch.